Assessment of the severity of stress in patients with type 2 Diabetes Mellitus depending on the level of vitamin D supply - Bobryk, Maryna; Komisarenko, Юлія (Psychosomatic Medicine and General Practice, 2024)
Nowadays the impact of the war’s stress factors on Ukrainian population continues. A number of psychopathological disorders are more common in patients with type 2 diabetes mellitus (T2DM) than in the general population. The impact of such disorders is underestimated, no more than 30% of the total number are actually detected, and more attention should be paid to their diagnosis in patients with T2DM. Methods. 121 patients with T2DM aged 19-75 were examined, of whom 54 men, 67 women. Assessment of vitamin D status was carried out using the "25-hydroxycalciferol" test, which was performed by the CLIA chemiluminescent immunoassay method. The assessment of the severity of stress was carried out using the DASS 21 questionnaire. The Spearman correlation coefficient was calculated to determine the direct or inverse dependence of the severity of stress on the level of 25-hydroxycalciferol. To analyze the relationship between the risk of severe and extremely severe stress with factor characteristics, the method of constructing logistic regression models was used. Results. A significant inverse relationship between the level of vitamin D and the severity of stress was observed. A strong statistical relationship between the risk of severe and extremely severe stress with the level of 25-OHD was revealed. The level of 25-OHD demonstrated a high prognostic value for the risk of severe and extremely severe stress. Discussion. The explanation for the inverse relationship between the level of 25-OH D and the severity of stress may lie in the presence of vitamin D receptors in the brain. It is known that D deficiency negatively affects the course of T2DM and must be corrected in time. Conclusions. In patients with T2DM, a significant inverse relationship between the level of 25-OH D and the degree of stress severity was observed. A level of 25-OH D ≤ 22.9 ng/ml is predictive for the risk of severe stress.